2014
DOI: 10.1039/c4ra08612k
|View full text |Cite
|
Sign up to set email alerts
|

Polylactide-b-poly(ethylene-co-butylene)-b-polylactide thermoplastic elastomers: role of polylactide crystallization and stereocomplexation on microphase separation, mechanical and shape memory properties

Abstract: PLA–PEB–PLA copolymers containing PLA segments with different stereo-regularities were prepared via the ROP of various lactides using PEB as the macromolecular initiator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…where ΔH cc refers to the crystallization enthalpy of biocomposites and ΔH 0 refers to the enthalpy value during 100% crystallization of PLA, which is 93.6 J/g [20]. X PLA refers to the weight ratio of PLA in PLA/BP biocomposites.…”
Section: Differential Scanning Calorimetry (Dsc) Analysismentioning
confidence: 99%
“…where ΔH cc refers to the crystallization enthalpy of biocomposites and ΔH 0 refers to the enthalpy value during 100% crystallization of PLA, which is 93.6 J/g [20]. X PLA refers to the weight ratio of PLA in PLA/BP biocomposites.…”
Section: Differential Scanning Calorimetry (Dsc) Analysismentioning
confidence: 99%
“…Adapted from [103] Another study demonstrated the influence of the stereocomplexation between PLLA and PDLA incorporated in triblock copolymers on microphase separation, mechanical and shape-memory properties. [104,105] The SMPs were synthesized by ROP of LLA and/or DLA with poly(ethylene-co-butylene) as initiator. An increased T m from 160 °C to 220 °C was detected for enantiomeric blends due to the formation of PLLA/PDLA stereocomplex crystallites.…”
Section: Thermoplastic Elastomeric Copolymer Networkmentioning
confidence: 99%
“…For instance, Yuan et al fabricated a fully bio‐based SMP by combining PLA, natural rubber, and thermoplastic vulcanizates together . Huang et al verified that SMP behavior can be observed from polylactide‐ b ‐poly(ethylene‐ co ‐butylene)‐ b ‐polylactide (PLA–PEB–PLA) triblock copolymers and that its performance can be controlled by adjusting the crystallizability of the PLA segments . Samuel et al reported a novel SMP composite that has multishape memory capability by integrating poly( l ‐lactide) (PLLA) with poly(methyl methacrylate) (PMMA) …”
Section: Introductionmentioning
confidence: 99%